The impact of training plyometric in the development of some requirements of performance skills of football players halls - Ibrahim, Layth Ismael; Allawy, Abduljabbar Kareem; Ahmed, Saif Saad; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The rapid development of the football game for the halls came as a result of the use of modern scientific methods in sports training, which contributed to the development of the skill and planning aspects and the success of any training process that depends on the foundations for the integrated preparation of each event, up to the player for the high level of performance and football for the halls from the collective games that have basic principles Multiple and depend on mastery, factors including following appropriate learning and training methods that achieve the required goals with economy in effort and time in the process of learning and training, and the importance of research lies in the application of plumeric exercises to develop the side The skill in the game of soccer for galleries by applying many methods to get out of the traditional and routine templates during training, especially that the chosen method constitutes the researcher the importance of being able to differ in the philosophy and strategy of this method and his money is important in advancing the football training process for the halls for the better and the problem of research lies in the weakness of the physical and skill side Among the football players in the halls and that the traditional training method does not develop the skill side in a large way, so the researcher considered the numbers of blue-collar exercises, which may positively affect the results of the matches and know their impact in developing the skill performance of football for the club. C. The research aims to develop some requirements for the skillful performance of the football players of the halls. The researcher used the experimental one- group approach using the tribal and dimensional measurements of the research sample from the players of the football education teams for the halls and after conducting research procedures and analyzing their results according to the research hypotheses established. The researcher concluded that exercises The palladium used has a positive effect in developing some of the basic skills of soccer for the halls, and the use of modern training tools and different spaces has the effect of developing the skillful performance of football players for the halls. The researcher recommends emphasizing the use of plumeric exercises according to some modern aids and tools and the use of new mechanisms and systems and innovative methods by investing play areas and using various special exercises in all conditions similar to competition in daily training units and the use of various and various exercises for its impact on the development of skill performance and thus the development of the performance of football players To the halls.